Penerapan Konsep Kalkulus dalam Kehidupan Sehari – Hari - Nurjana Nuraita; Sutrisna Sutrisna; Aryasti Salsa Sabilla; Iwan Cakrayana; Ul’fah Hernaeny (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Basic mathematical principles are applied in daily activities, especially in the field of economics, and are an important source in teaching and learning activities in the field of mathematics. This research aims to explore the basic mathematical principles of economics to support and reference in learning activities. The method used in the research is based on a literature review study. Based on the research conducted, there are six main topics discussed regarding basic mathematical concepts in economics, namely a) variables, constants, coefficients and parameters; b) equations and inequalities; c) set theory concepts; d) real number system; e) power rules, roots, factorization, as well as f) fractions, decimals and percentages.